Public diplomacy and Ethio-Egyptian relation; enhancing mutual understanding on the Grand Ethiopian Renaissance Dam - Muluken Gemechu Worku (Cogent Social Sciences, 2024)
GERD has been a source of tension and a diplomatic deadlock between Egypt and Ethiopia. Diplomacy and cooperation are the only means to resolve these issues. The inability to recognize the current reality that emanates from contradictory narration leads Ethiopia and Egypt relations on the GERD into full mistrust and misconception, and even moving toward confrontation. Accordingly, this study was intended to examine how public diplomacy enhances mutual understanding between Ethiopia and Egypt on the GERD. This study employed a qualitative research approach with in-depth literature review. The findings of the research reveal that securitization, counter-securitization narration, and over-politicization are dominant in the GERD at the cost of the objective reality that muddies Nile water utilization. Hence, the study identified strong popular narratives based on ultra-nationalism and political rhetoric on the GERD that were built by successive government officials, and media, scholars based on past and current events deepened the mistrust. The researcher recommends that Ethiopia and Egypt should widen diplomatic efforts in addition to conventional diplomacy by implementing public diplomacy elements to understand their vice-versa genuine concern and build confidence in GERD, which ultimately fosters effective cooperation.